A Business Model View of Strategy. (5th May 2020) - Lanzolla, Gianvito; Markides, Constantinos
Abstract: We argue that while the business model construct may not be entirely new, it can still provide a novel lens, complementary to Resource Based View and Market Positioning, to develop new theoretical insights in strategy. We propose that the consideration of interdependencies among the activities of a business model provides such a lens. We show that by starting strategy development with interdependencies among activities, we can: (1) develop new insights on how to build superior strategies; and (2) explain company performance variance especially when heterogeneity in resources and capabilities is not strong and barriers to imitation are weak. Overall, we propose that a promising research avenue for the business model literature is to integrate complexity theory with demand‐side and supply side theories of strategy to generate more nuanced insights on what activities to connect and how to develop superior interdependencies among activities that can form the basis of superior strategies.